GROUP COUNSELLING SKILLS AMONG COUNSELLING TRAINEES - Aslina Ahmad; Pau Kee; Mohammad Aziz Shah Mohamed Arip, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Abstract: Group counselling is one of the important courses in counselling program. In order to ensure that counselling trainees are equipped with the skills to conduct counselling groups, this research investigated the group counselling group skills that were preferably used by the trainees. An education university in Malaysia that enrolled a number of counselling trainees was chosen purposive method. A number of 40 counselling trainees were involved in the survey, and 6 were interviewed. Results showed that the most frequently group counselling skills utilized is interviewing skills, less on focusing, and cutting off. The respondents also mentioned about their difficulty in utilizing group skills as interrupting people while talking is considered as rude in the society. Another significant aspect mentioned by the respondents were lack of focus in the session as they were more prone thinking of the appropriate response to be given in the session. Suggestion and implication were given at the end of the paper.